Mongolia : Measuring the Output Gap - Bersch, Julia (IMF Working Papers; Working Paper ;, 2011)
This paper compares the output gap estimates for Mongolia based on a number of different methods. Special attention is paid to the substantial role of mining in the Mongolian economy. We find that a Blanchard and Quah-type joint model of output and inflation provides a more robust estimate of the output gap for Mongolia than the traditional statistical decompositions.